Epigenetic mechanisms underlying learning and the inheritance of learned behaviors. Issue 2 (February 2015) - Dias, Brian G.; Maddox, Stephanie A.; Klengel, Torsten; Ressler, Kerry J.
Highlights Fear conditioning is an excellent tool to understand epigenetic memory regulation. Epigenetic marks in gametes may allow signals to be passed to the next generation. Noncoding RNA provides a mechanism by which signals may be transmitted across genomes. Epigenetics enhances understanding of gene–environment interactions in psychiatry.